See how they run - Carter, Ally (Carter, Ally. Embassy Row, 2017)
Grace Blakely believed that finding the truth about her mother's murder would finally give her peace, but now she knows that it is only the beginning of the secrets that will dominate her life--and make her a target on Embassy Row in Adria.